2013
DOI: 10.1002/pmic.201200431
|View full text |Cite
|
Sign up to set email alerts
|

Crop seed oil bodies: From challenges in protein identification to an emerging picture of the oil body proteome

Abstract: Oleaginous seeds store lipids in specialized structures called oil bodies (OBs). These organelles consist of a core of neutral lipids bound by proteins embedded in a phospholipid monolayer. OB proteins are well conserved in plants and have long been grouped into only two categories: structural proteins or enzymes. Recent work, however, which identified other classes of proteins associated with OBs, clearly shows that this classification is obsolete. Proteomics-mediated OB protein identification is facilitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 93 publications
5
42
3
Order By: Relevance
“…6A). In a typical LD topology, neutral lipids are covered by a polar membrane shell (Jolivet et al, 2013). Since smaller LDs contain a higher proportion of polar membrane lipids than larger LDs, this suggests that the LDs in SL-exposed cells are smaller than those induced by N starvation, which was consistent with microscopic examinations (Fig.…”
Section: Lds In Sl-exposed Cells Contain Tags and Polar Lipids Of Mossupporting
confidence: 78%
See 1 more Smart Citation
“…6A). In a typical LD topology, neutral lipids are covered by a polar membrane shell (Jolivet et al, 2013). Since smaller LDs contain a higher proportion of polar membrane lipids than larger LDs, this suggests that the LDs in SL-exposed cells are smaller than those induced by N starvation, which was consistent with microscopic examinations (Fig.…”
Section: Lds In Sl-exposed Cells Contain Tags and Polar Lipids Of Mossupporting
confidence: 78%
“…Oil accumulation is associated with the formation of lipophilic droplets, called lipid droplets (LDs [or oil bodies or oleosomes]; Jolivet et al, 2013). LDs are specialized intracellular organelles made of a neutral lipid core surrounded by a membrane lipid coat in which proteins are embedded (Huang, 1996).…”
mentioning
confidence: 99%
“…To understand the diverse functions of lipid droplets, an array of proteins have been identified that are associated with lipid droplets from different cell types and organisms (Cermelli et al, 2006;Hodges and Wu, 2010;Yang et al, 2012;Jolivet et al, 2013). In higher plants, oleosins, caleosins, steroleosins, and other seedspecific lipid droplet proteins have been widely recognized for their role in lipid compartmentalization in oilseeds and some floral tissues, such as anther and pollen (Huang, 1992;Tzen and Huang, 1992;Frandsen et al, 2001;Lin et al, 2005;Huang et al, 2013).…”
mentioning
confidence: 99%
“…Drying management may brought about over expression of DGAT (Weselake et al 2008). Oil bodies are the main form of oil in mature seed, internally containing liquid TAG and externally forming phospholipid monolayer (Jolivet et al 2013). We identified the presence of oleosins and caleosins proteins in camellia seed, and involved in 4 oleosin unigenes (CL734Contig1, CL422Contig1, CL32127Contig1 and CL25464Contig1) with expression over 1000 RPKM in average (Table 7, S4).…”
Section: Discussion Fatty Acids Biosynthesis and Accumulationmentioning
confidence: 99%